A phase I clinical study of vaccination of melanoma patients with dendritic cells loaded with allogeneic apoptotic/necrotic melanoma cells. Analysis of toxicity and immune response to the vaccine and of IL-10-1082 promoter genotype as predictor of disease progression - von Euw, E.M. (2008)
Background: Sixteen melanoma patients (1 stage IIC, 8 stage III, and 7 stage IV) were treated in a Phase I study with a vaccine (DC/Apo-Nec) composed of autologous dendritic cells (DCs) loaded with a mixture of apoptotic/necrotic allogeneic melanoma cell lines (Apo-Nec), to evaluate toxicity and immune responses. Also, IL-10 1082 genotype was analyzed in an effort to predict disease progression. Methods: PBMC were obtained after leukapheresis and DCs were generated from monocytes cultured in the presence of GM-CSF and IL-4 in serum-free medium. Immature DCs were loaded with gamma-irradiated Apo-Nec cells and injected id without adjuvant. Cohorts of four patients were given four vaccines each with 5, 10, 15, or 20 × 106 DC/Apo-Nec cell per vaccine, two weeks apart. Immune responses were measured by ELISpot and tetramer analysis. Il-10 genotype was measured by PCR and corroborated by IL-10 production by stimulated PBMC. Results: Immature DCs efficiently phagocytosed melanoma Apo-Nec cells and matured after phagocytosis as evidenced by increased expression of CD83, CD80, CD86, HLA class I and II, and 75.2 ± 16% reduction in Dextran-FITC endocytosis. CCR7 was also up-regulated upon Apo-Nec uptake in DCs from all patients, and accordingly DC/Apo-Nec cells were able to migrate in vitro toward MIP-3 beta. The vaccine was well tolerated in all patients. The DTH score increased significantly in all patients after the first vaccination (Mann-Whitney Test, p < 0.05). The presence of CD8+T lymphocytes specific to gp100 and Melan A/ MART-1 Ags was determined by ELISpot and tetramer analysis in five HLA-A*0201 patients before and after vaccination; one patient had stable elevated levels before and after vaccination; two increased their CD8 + levels, one had stable moderate and one had negligible levels. The analysis of IL-10 promoter -1082 polymorphism in the sixteen patients showed a positive correlation between AA genotype, accompanied by lower in vitro IL-10 production by stimulated PBMC, and faster melanoma progression after lymph nodes surgery (p = 0.04). With a mean follow-up of 49.5 months post-surgery, one stage IIC patient and 7/8 stage III patients remain NED but 7/7 stage IV patients have progressed. Conclusion: We conclude that DC/Apo-Nec vaccine is safe, well tolerated and it may induce specific immunity against melanoma Ags. Patients with a low-producing IL-10 polymorphism appear to have a worst prognosis. © 2008 von Euw et al; licensee BioMed Central Ltd.